Flipped Classroom Approach in Teaching Biology: Assessing Students’ Academic Achievement and Attitude Towards Biology - Malto, G A O; Dalida, C S; Lagunzad, C G B (KnE Social Sciences, 2018)
flipped classroom is a specific model of blended learning that involves online delivery of content and instruction while students are at home or outside the school. This model is combined with a face-to-face teacher-guided instruction where students complete projects and tasks inside the classroom. The research investigates the effect of the flipped Classroom Approach on students’ academic achievement and in attitude towards Biology. The study also aims to collect data from teacher observations that can provide an unbiased and multi-perspective assessment of the implementation of the flipped Classroom Approach based on the following criteria: (1) academic involvement; (2) student-peer-teacher involvement; and (3) time allotment. The quasi-experimental design was used in this study. Two randomly assigned groups of students participated: (I) the Traditional Group (TG) and; (II) the flipped Classroom Group (FCG). The students’ academic achievement in Biology was assessed through descriptive and inferential statistics. Also, the students’ interest and confidence levels in biology were measured. The results showed statistically significant difference in favor of the FCG, where students performed better in both lower and higher order thinking skills. Moreover, FCG obtained significantly higher gain scores than TG. In terms of attitude, FCG gained a significantly higher level of interest and confidence in the subject matter after the intervention. Analysis of the results of multi-perspective assessment revealed that teacher-observers generally perceived the flipped Classroom Approach as a novel way of teaching that promotes highly evident collaborative and active student-teacher and student-student interactions. The flipped classroom instruction also provided opportunities for scaffolding and differentiation, which helped the teacher address individual needs of students. Moreover, as the students gained higher levels of interest and confidence in the subject matter, they became more actively engaged in the performance of activities and building of ideas, and more participative and articulate during small group discussions. Keywords: blended learning; flipped classroom; academic achievement; students’ attitude; quasi-experimental.